Partial Unilateral Lentiginosis Successfully Treated with the Combination of 511 nm and 578 nm Copper Bromide Laser in an Indonesian Woman - Hindritiani R; Widjaya MRH; Puspitosari D; Rizqandaru T; Ruchiatan K (Dove Medical Press, 2023)
Reti Hindritiani, Muhamad Radyn Haryadi Widjaya, Diah Puspitosari, Trustia Rizqandaru, Kartika Ruchiatan Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Reti Hindritiani, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Bandung, West Java, Indonesia, 40161, Tel +62222032426 ext. 3449, Fax +62222032426, Email r.hindritiani@unpad.ac.idAbstract: Partial unilateral lentiginosis (PUL) is a pigmentation disorder characterized by multiple lentigines restricted to the normal skin in a unilateral and segmental pattern. Various lasers have been used for the treatment of this pigmented disorders, one of which is the copper bromide (CuBr) laser, which emits a dual-wavelength beam at 511 nm and 578 nm. A 35-year-old woman presented with multiple brown macules with a sharp demarcation from the midline of the forehead to the right cheek in a dermatomal distribution. Histopathological results showed increased melanin pigmentation in the basal layer with elongated rete ridges, supporting the diagnosis of PUL. Following photoprotection and skin priming, CuBr laser treatment was performed in two steps using 511 nm and 578 nm wavelength as the first and second steps, respectively, with the second step delivered immediately after. Clinical improvement was achieved after two sessions of treatment at a one-month interval, as shown by an increasing lightness value (L*) in spectrophotometry. No side effects, such as hyperpigmented macules, was observed. The patient also expressed satisfaction at her brighter facial skin. A sustainable favorable result persisted after six months of laser treatment. Interactions between cutaneous vasculature and melanocytes can affect the development of pigmented lesions. Melanocytes express the functional vascular endothelial growth factor receptor (VEGF) and are responsive to angiogenic factors. Ideally, these conditions should be treated with a dual-wavelength CuBr laser. The combination of 511 nm and 578 nm CuBr laser showed favorable results, supporting its potential as an effective treatment choice for PUL.Keywords: copper bromide, dual wavelength, effective, laser, partial unilateral lentiginosis